Burden of gastroesophageal reflux disease among women of childbearing age, with projections to 2050: an analysis of the Global Burden of Disease study 2021 - Zhou, Siyu; Wang, Yanping; Hou, Nengyi; Hu, Kun; Jiang, Shun; You, Junzhao; Tang, Hongtao; Zeng, Jie; Pang, Minghui (Frontiers in Global Women's Health, 2025)
BackgroundGastroesophageal reflux disease (GERD) is a common chronic digestive disorder characterized by the reflux of gastroduodenal contents into the esophagus, causing uncomfortable symptoms and potential tissue damage. It affects over 1 billion people worldwide, imposing substantial economic and health burdens. Notably, women of childbearing age face unique challenges due to hormonal fluctuations, pregnancy, and gender-specific social roles, yet systematic global analyses of GERD burden in this population remain scarce.MethodsThis study evaluated the global, regional, and national burden of GERD among WCBA from 1990 to 2021 and projected trends through 2050. Data were sourced from the 2021 Global Burden of Disease (GBD) study, including incidence, prevalence, years lived with disability (YLDs), and their age-standardized rates. Temporal trends were analyzed using joinpoint regression (average annual percentage change, AAPC), and future projections were generated via Bayesian age-period-cohort models. Associations with the Socio-demographic Index (SDI) were explored.ResultsGlobally, the number of incident and prevalent GERD cases among WCBA increased by 64.09% and 66.44% from 1990 to 2021, reaching almost 99.1 million and 245.2 million in 2021, respectively. The AAPCs for age-standardized incidence rate (ASIR), age-standardized prevalence rate (ASPR), and age-standardized YLD rate (ASYR) were 0.24, 0.23, and 0.23, respectively. Regionally, South Asia had the highest absolute burden, while Tropical Latin America had the highest ASRs. Nationally, the Republic of India reported the highest incidence, the People's Republic of China the highest prevalence, Brazil the highest ASRs, and Norway the lowest. SDI was negatively correlated with GERD burden, with the most notable upward trends in middle SDI regions. By age, burden increased with age and peaked in the 25–29 years group. Joinpoint analysis showed accelerated growth post-2011. Projections to 2,050 forecast continued rises in incidence, prevalence, and ASRs.ConclusionThe global GERD burden among WCBA is increasing, with marked regional, national, and SDI-related disparities. Physiological characteristics, lifestyle changes, and healthcare accessibility are key drivers. Targeted interventions such as strengthening primary care, lifestyle guidance, and region-specific policies are critical to mitigate risks. This study fills a research gap, providing evidence to inform global strategies for GERD prevention and management in this population.